PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KOMITMEN ORGANISASIONAL DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA BPD BALI CABANG RENON - Aditya Wirapranaya, I Gde Nyoman; Supartha, I Wyn Gede (E-Jurnal Manajemen, 2016)
This study aims to determine the effect of transformational leadership on organizational commitment and OCB. This research was conducted at PT. Regional Development Bank Branch Renon Bali. Sampling method used in this study sample is saturated. Data were collected using interviews and questionnaires. The respondents of this study were 89 employees of PT. Regional Development Bank Branch Renon Bali. Data analysis techniques used in this research is path analysis path. The results of transformational leadership and significant positive effect on organizational commitment with a beta value of 0.579. The results of transformational leadership and significant positive effect on OCB with a beta value of 0.504. The results of organizational commitment and significant positive effect on OCB with a beta value of 0.359.
Keywords: transformational leadership, organizational commitment, organizational citizenship behavior